DETERMINATION OF BREACH IN ORAL LENDING AGREEMENTS WITHOUT AGREEMENT OF RETURN TIME REVIEWED FROM THE AGREEMENT LAW - Satria Gunawan; Gunawan Djajaputra (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The agreement in its implementation constitutes a binding legally binding between one party to another party who enters into the agreement. Agreements can be made orally or in writing provided that they do not conflict with the provisions stipulated by laws and regulations. Sometimes in the implementation of the agreement, the parties sometimes do not carry out the contents of the agreement, so that in practice the legal system in Indonesia is known as a default or broken promise. In 2011, there was a dispute between Manginar Sagala and Absen Malau regarding the loan provided by Manginar Sagala to Absen Malau. In the loan agreement, it was agreed that Manginar Sagala would lend Rp. 137,000,000. - (one hundred thirty seven million rupiah) to Absen Malau where this agreement was made orally. However, until 2017, Absen Malau had no good faith intention to repay the loan and challenged him by saying that he would just put me in prison. On December 4, 2020 Manginar Sagala through his attorney sent a letter of warning/subpoena to Absen Malau but there was no response at all from Absen Malau. So that Manginar Sagala sued Absen Malau at the Medan District Court with a lawsuit that Absen Malau had defaulted (broken promise). What is the formulation of this research problem regarding the provisions regarding verbal loan agreements? As well as how is the determination of default in the loan agreement orally without an agreed return time in terms of the law of the agreement? The method used in this research is the normative legal method. The results of the analysis show that the provisions regarding verbal lending and borrowing agreements when viewed from the form of the agreement, whether written or oral or non-contractual, will not affect the binding strength of an agreement as long as the essence of the agreement made does not conflict with applicable legal principles.